Effect of land-use practices on species diversity and selected soil property in Somodo Watershed South-Western Ethiopia. - Leta Hailu; Gizaw Tesfaye; Kalkidan Fikirie; Yalemtsehay Debebe (PLoS ONE)
This study was conducted in Somodo Watershed to investigate the land-use practices and its effect on species diversity and selected soil properties. Field observation was carried out to identify existing land-use practices following a transect line. A total of 20 plots (10 × 10) m2 were sampled from plots exhibiting different land-use practices found in the watershed in order to evaluate species richness and diversity. Soil samples were also collected from each plot. The soil samples were analyzed following standard laboratory procedures. The result of the analysis showed that there was a significant difference (p<0.05) in species diversity and richness among different land-use practices. Coffea arabica was dominant in homestead gardens and natural forests while Grevillea robusta showed had maximum richness in plantations and farm forests in the Watershed. Furthermore, home garden agroforestry practice was significantly (p<0.05) affected soil pH compared to other land-use systems (cultivated land, natural forest, and plantation forest. While Organic carbon (OC), Total nitrogen (TN), and Carbon to Nitrogen ratio (C: N) did not show significance difference among land-use systems in the watershed. The study has concluded that different land-use practices had a positive impact on sustaining species diversity, richness, and improve soil properties. Therefore, the study suggests that improving and expanding home garden agroforestry practices in the area are indispensable for environmental protection and soil fertility enhancement.